Measuring service quality in guesthouses in Kimberley through the use of the Servqual instrument - Mvana, M. (My University, 2013)
The growth of the tourism industry led to the development of various different types of tourism products. In order to remain competitive it is important that tourism products provide high-quality services for tourists. Tourists are, however, becoming more demanding due to higher education levels, more sophisticated tourists that travel more and are more exposed to various types of experiences. It is therefore important that tourism products satisfy the expectations of the guest to increase loyalty levels as well as return to the product. It is difficult today to exceed the expectations of the guest but high levels of service quality can make a difference in the customer experience and it is thus worthwhile to go the extra mile for guest. Although service quality has been measured in various research studies it has not been measured for the guesthouses in Kimberley and this information can be to the advantage of the tourism products as well as to that of Kimberley as a destination. The main aim of this study was to measure service quality levels of guesthouses in Kimberley based on the SERVQUAL instrument to gain a competitive advantage over similar tourism products and to assist these products in meeting and exceeding guest’s expectations. Questionnaires were distributed at participating guesthouses in Kimberley. A total of 500 questionnaires were distributed among guests guest of which 450 were used in the analyses. The questionnaire was divided into four sections, namely socio-demographic information, the expectations of guest, the perceptions of guest and the overall service quality of the guesthouse. The data resulting from the questionnaires was captured and analysed by means of descriptive and exploratory analyses in SPSS. A factor analysis was applied to the 29-attribute scale measuring service expectations and perceptions. The paired-samples t-tests were used to determine the differences in the expectations and the perceptions. The multiple regression analysis was done to determine the aspects best predicting the overall service quality levels in the guesthouses. From the descriptive analyses it was clear that the two main expectations from guests include the following: employees will be willing to serve and that employees will always be available when needed. The highest mean value was obtained for the first aspect mentioned. In terms of the perceptions, the main perceptions of the guest included: employees gave individualised attention, the operating hours of the guesthouse are convenient and the guesthouse provides a safe and secure environment. In the case of perceptions, the aspect that yielded the highest mean was: employees are always available when needed. The paired t-test revealed very few differences in expectations versus perceptions and this indicated that respondents are satisfied with the service levels and that the guesthouses did better than expected. The factor analyses revealed the following five factors: Tangibles, Adequacy, Understanding, Assurance and Convenience. Before visiting the guesthouse it was clear that Assurance made the strongest contribution to overall service quality but after visiting the guesthouse Understanding and Convenience made the strongest contribution to overall service quality; thus indicating what is important to the guests. This study contributes to the existing body of knowledge in guesthouse management but also to service quality in accommodation establishments such as guesthouses. Knowing that service levels in the participating guesthouses adhered to the needs of the current guests guest is encouraging, but these establishments need to plan strategically for when these guests guest overnight again and might expect something additional, extra or even different.
M. Tech. (Tourism and hospitality Management, Faculty of Human Sciences)|cVaal University of Technology
Keywords: South Africa tourist industry; Service quality; SERVQUAL; Guest house management; 647.940968711; Boardinghouses -- Management.; Hospitality industry -- South Africa